Fresh Chicken as Main Risk Factor for Campylobacteriosis, Denmark - Wingstrand, Anne (Centers for Disease Control and Prevention, 2006)
We report the findings of a case-control study of risk factors for sporadic cases of human campylobacteriosis in Denmark. In 3 different analytical models, the main domestic risk factor identified was eating fresh, unfrozen chicken. Specifically, 28 of 74 domestically acquired case-patients were exposed to fresh chicken compared with 21 of 114 controls (multivariate matched odds ratio 5.8; 95% confidence interval 2.1–15.9). In contrast, a risk from eating other poultry, including previously frozen chicken, was only indicated from borderline significant 2-factor interactions. The marked increase in consumption of fresh, unfrozen poultry in Denmark during the 1990s likely contributed substantially to the increasing incidence of human campylobacteriosis in this period.